Thermodynamic and physical properties for high pressure process design - Knez Marevci, Maša (visokošolska dela, 2014)
The thesis is comprised of three main categories. The first part of dissertation covers investigations of phase equilibria of compounds from natural materials in conventional and also non conventional supercritical fluids. In details, the impact of pressure and/or temperature on the system behaviour (miscibility, solubility, phase inversion) is investigated, quantitative and qualitative analyses to evaluate and identify compounds contained after performing preliminary extraction experiments from different natural tissues are presented. The impact of operating parameters (pre-treatment of the raw material with SFE; different extraction solvents: propane, CO2, non conventional SCFs; different extraction temperatures and pressures) on extraction kinetics is observed. Following substances were taken into consideration: vanillins, caffeine, carnosoic acid extract and lecithin. Second part of dissertation covers studies of phase equilibria of the systems bio oil/gas, which is crucial in biorefinery process design. In this part of dissertation, which covers studies of phase equilibria of binary and ternary systems, the impact of pressure and/or temperature on the system behaviour (miscibility, solubility, phase inversion) for binary system bio oil/supercritical fluid (bio oil/CO2) and (bio oil/H2) was studied. Additionally, phase behaviour of ternary systems of (bio oil/diesel/CO2) and (bio oil/tail water/CO2) under the impact of pressure and/or temperature is observed. These data are of a high importance for bio refineries as an important part of necessary sustainable development. In recent years, studies on biodiesel synthesis have focused on development of process intensification technologies to resolve some of these issues. Fundamental data to design fractionation process of components of bio oil are crucial for an efficient hydrogenation process of bio oil. In the third part of dissertation observation of phase equilibria and determination of the parameters like diffusion coefficient, density and viscosity for the systems polymer/CO2 at elevated pressures is investigated. An overview of different methods applied to determine the parameters like diffusion coefficient, density and viscosity of the systems polymer (PEG)/CO2 at elevated pressures is offered. Observation of phase equilibria of the binary system PEG/CO2, determination of the impact of pressure and/or temperature on the system behaviour (miscibility, solubility, phase inversion), determination of thermodynamically and physically properties of the system with new applicative methods and finally, comparison of the results obtained by different methods is provided. The interfacial tension (IFT) at the (PEG)/CO2 interface has been determined by using an experimental technique developed to study the interfacial interactions of the liquids in equilibrium with gas in a glass-windowed equilibrium cell by the means of Capillary Rise (CR) method. Advantages and disadvantages of methods that were applied are exposed and discussed.
Keywords: bio oil; capillary rise methode; CR method; diffusin coefficient; difuzijski koeficient; ekstrakcija; extraction; fazna ravnotežja; fizikalni podatki; metoda kapilarnega dviga; načrtovanje; naravni materiali; natural materials; phase equilibria; površinska napetost; superkritični fluidi; surface tension; termodinamski podatki; viscosity; viskoznost; visokotlačni procesi